MEKANISME PELAKSANAAN PENYELESAIAN SENGKETA MELALUI BAPMI PADA PERDAGANGAN SAHAM DI PASAR MODAL - khadijatul musanna (KASBANA, 2023)
The purpose of this study is to examine the procedures and cases of capital market dispute settlement which were resolved through the Indonesian Capital Market Arbitration Board. Formally, the capital market is an activity related to public offerings and securities trading, one of which is stock trading in the capital market. In this study using normative juridical research methods. The data obtained comes from primary data, namely data from the Indonesian Capital Market Arbitration Board, while secondary data comes from literature related to law related to dispute resolution. The results of the research obtained are that in BAPMI there are not many cases that have been completed, the case of pawning shares is one of the cases that has been successfully resolved through the media. The BAPMI mediation procedure consists of registration, verification, appointment of mediator and peace agreement. With regard to other cases of PT Nikko Securities Indonesia and PT. Bank Permata Tbk is a case that has been decided by BAPMI, but was canceled and submitted to the District Court.